O efeito da idade relativa no voleibol brasileiro de elite - Otoni Parma, J.; Macedo Penna, E. (Journal of Physical Education, 2018)
The relative age effect (RAE) refers to the advantage of the athletes born on the first months of the sport selection period compared to those born months later during such a selection process, which tends to favor athletes who are in a more developed maturational stage or those who have more advanced physical development compared to their younger counterparts born in the same year. This advantage occurs mainly in sport whose physical characteristics are determinant for obtaining success, such as volleyball, which leads to the premature exclusion or dropout of potential talents from sport. This study aims at assessing the RAE presence in Brazilian men`s and women`s elite volleyball by analysing the number of athletes who were born in each trimester of the year and had been ranked to the main national Super Leagues. The results showed no effect related to the RAE in Brazilian women`s elite volleyball, whereas there was a higher representation of male athletes born in the first trimester compared to the ones born on the 3rd and 4th trimesters. These results point to a need for better understanding the causes and consequences of RAE in Brazilian men`s volleyball in order to avoid premature exclusion or dropout of potential talents, thus, enabling an even greater development of this sport in the country.